2022
DOI: 10.1155/2022/3144545
|View full text |Cite
|
Sign up to set email alerts
|

Calculation Model of the Axial Dispersion Distribution of Cylindrical-Warhead Fragments

Abstract: The dispersion distribution characteristics of prefabricated fragments from an improvised explosive device (IED) are essential in defense technology development. To improve warhead design, it is essential to predict a fragment’s velocity and dispersion distribution accurately. This paper investigates a fragment’s flying angle from a detonated warhead with a cylindrical charge under a one-end central detonation. A modified formula for calculating the fragment dispersion distribution at each axial position of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The initial fragment velocity and the spatial distributions of fragments enable the complete characterization of damage that a preformed fragment warhead can inflict [24]. Due to the axial sparsity, the fragment dispersion distribution at the ends of the cylindrical warhead with end-point initiation is not uniform [14]. A series of semi-empirical formulas have been previously proposed.…”
Section: Damage Field Of the Preformed Fragment Lypgwmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial fragment velocity and the spatial distributions of fragments enable the complete characterization of damage that a preformed fragment warhead can inflict [24]. Due to the axial sparsity, the fragment dispersion distribution at the ends of the cylindrical warhead with end-point initiation is not uniform [14]. A series of semi-empirical formulas have been previously proposed.…”
Section: Damage Field Of the Preformed Fragment Lypgwmentioning
confidence: 99%
“…Calculation of Fragment Velocity Randers-Pehrson [8], Charron [9], Zulkoski [10], and Huang [12] et al proposed the formulas to predict the axial distribution of the initial fragment velocities when a cylindrical charge preformed fragment warhead detonates at the one-end central by modifying the Gurney velocity [6]. It was confirmed that Huang's formula was more accurate [14,15], which is expressed as…”
Section: Damage Field Of the Preformed Fragment Lypgwmentioning
confidence: 99%
See 1 more Smart Citation
“…König [7] and Huang et al [8] studied a formula for the fragment dispersion angle of cylindrical warheads with end effects by experimental testing and numerical simulation. Jiang et al [9] studied the dispersion distribution of fragments under the charge of cylindrical shell during central initiation at one end. Wang et al [10] studied a calculation method of full-scale fragment distribution based on the CDEM method.…”
Section: Introductionmentioning
confidence: 99%